Headache Associated with Myasthenia Gravis: The Impact of Mild Ocular Symptoms. (29th June 2011) - Nishimoto, Yoshinori; Suzuki, Shigeaki; Utsugisawa, Kimiaki; Nagane, Yuriko; Shibata, Mamoru; Shimizu, Toshihiko; Suzuki, Norihiro
Abstract : Myasthenia gravis (MG) patients visiting outpatient clinics frequently complain of headache. However, there have been few reports on the relation between chronic headache and myasthenia gravis (MG). We aimed to investigate whether MG symptoms affect the development or worsening of chronic headache. Among the 184 MG patients who were followed at the MG clinics, tension-type headache was observed in 71 (38.6%) patients and 9 (4.9%) complained of migraine. Twenty-five (13.6%) complained that headache appeared or was exacerbated after the MG onset. The investigation into differences in the clinical characteristics of the MG patients showed that women tended to suffer from MG-associated headache more often than men. Logistic regression analyses revealed that female gender and mild ocular symptoms were independently predictive of headache associated with MG. Our results suggest that treatment of chronic headache should be required to improve the quality of life in MG patients.